Implementation of Large-Scale Social Restrictions Policy (PSBB) in Bogor District Government - Retnowati WD Tuti; Ma'mun Murod; Tria Patrianti (Universitas Padjadjaran, 2020)
Large-scale Social Limitation (hereinafter referred to as PSBB) is one form of concern. The government and local governments are Pendemic throughout Indonesia and the world, namely Pandemic Corona Virus Disease (Covid-19). Bogor Regency, which is one of the buffer cities of the Republic of Indonesia, is an area that is quite vulnerable in spreading the Corona virus. Why? because many DKI Jakarta employees / laborers live in Bogor Regency, whose mobility is very high. With the birth of Regent Regulation No. 16 of 2020 concerning Implementation of Large- Scale Social Restrictions in Handling COVID-19 in order to conserve the use of Covid 19. The purpose of this study is to analyze the Implementation of Large Scale Social Limitation Policies in the Government of Bogor Regency. This research method uses Qualitative Methods with Literature Study research methods. (Huberman, Miles, 1994). The technique of inviting data is by searching Scientific Journals, Online Mass Media, Legislation and Books. The technique to determine Online Media by Pusposive, while for data analysis using Nvivo 12 Plus. Test the validity of the data by testing the data source. The results of the study show that the implementation of the Large-Scale Social Limitation Policy in the Bogor District Government has not yet proceeded, starting from the clash of authority between the Central Government and the Regional Government so that it cannot make improvements, and many more are in accordance with the provisions of Covid-19 and its distribution. Social assistance to the community.